The MAGPI survey: Science goals, design, observing strategy, early results and theoretical framework. (26th July 2021) - Foster, C.; Mendel, J. T.; Lagos, C. D. P.; Wisnioski, E.; Yuan, T.; D'Eugenio, F.; Barone, T. M.; Harborne, K. E.; Vaughan, S. P.; Schulze, F.; Remus, R.-S.; Gupta, A.; et al.
Abstract: We present an overview of the M iddle A ges G alaxy P roperties with I ntegral Field Spectroscopy (MAGPI) survey, a Large Program on the European Southern Observatory Very Large Telescope. MAGPI is designed to study the physical drivers of galaxy transformation at a lookback time of 3–4 Gyr, during which the dynamical, morphological, and chemical properties of galaxies are predicted to evolve significantly. The survey uses new medium-deep adaptive optics aided Multi-Unit Spectroscopic Explorer (MUSE) observations of fields selected from the Galaxy and Mass Assembly (GAMA) survey, providing a wealth of publicly available ancillary multi-wavelength data. With these data, MAGPI will map the kinematic and chemical properties of stars and ionised gas for a sample of 60 massive ( >7 × 10^10 M_ ) central galaxies at 0.25 < z <0.35 in a representative range of environments (isolated, groups and clusters). The spatial resolution delivered by MUSE with Ground Layer Adaptive Optics ( 0.6-0.8 arcsec FWHM) will facilitate a direct comparison with Integral Field Spectroscopy surveys of the nearby Universe, such as SAMI and MaNGA, and at higher redshifts using adaptive optics, for example, SINS. In addition to the primary (central) galaxy sample, MAGPI will deliver resolved and unresolved spectra for as many as 150 satellite galaxies at 0.25 < z <0.35, as well as hundreds of emission-line sources at z < 6 . This paper outlines the science goals, survey design, and observing strategy of MAGPI. We also present a first look at the MAGPI data, and the theoretical framework to which MAGPI data will be compared using the current generation of cosmological hydrodynamical simulations including EAGLE, Magneticum, HORIZON-AGN, and Illustris-TNG . Our results show that cosmological hydrodynamical simulations make discrepant predictions in the spatially resolved properties of galaxies at z≈ 0.3 . MAGPI observations will place new constraints and allow for tangible improvements in galaxy formation theory.